Economist's miscellany - Basu, Kaushik (New Delhi, 2011)
Philosophy has to be deductive, poetry romantic, plays and fiction humorous, and politics intriguing if they are to catch my attention,' writes Kaushik Basu. All these interests are on display in An Economist's Miscellany , which brings together an eclectic collection of writings on the world of academe, politics, and policy. Basu sweeps a vast canvas, from recession and the global economic crises, foreign policy, and financial scams, to art and aesthetics. In this slim volume he offers unique glimpses of his inner world-his excitement and apprehensions on moving from academics to government and policy making; his thoughts on his mother turning 90; and persons, ideas, and books that have influenced him. An Economist's Miscellany also puts on display his literary forays-translations of two Bengali short stories and a four-act play. The stories are hilarious and yet have scathing social content: one illustrates the intricacies of moneylending and the debt trap, while the other provides a critique of religious obscurantism and bigotry. The play, light-hearted and facetious, presents a slice of everyday life in an academic setting. Basu has written extensively on diverse fields of economics and, more generally, the social sciences. This collection displays the full range of his wisdom and humour, and above all his celebration of everyday human follies and foibles. Memoirs, travel writing, fiction, essays, and games-they are all here, and will give readers not just the pleasure of reading but also ideas and riddles to ponder over.
Keywords: Basu, Kaushik-Economic writings